Design of Hand Stability Measuring Device for Shooting Training at the Air Force Academy - Ramananda, Muhammad Syafiqi; Gastomo, Bambang (Akademi Angkatan Udara, 2022)
The purpose of this study was to design a shooting hand vibration measuring device using a MPU6050 accelerometer sensor based on the Arduino Uno microcontroller. As soon as there is a vibration on the hand, the MPU6050 accelerometer sensor will measure the vibration and send the data to the Arduino Uno mycorocontroller to be displayed on the Liquid Cryatal Display (LCD) screen and sound the buzzer component if the detected vibration has exceeded the limit of 0.3 G on each axis. It is hoped that the creation of this tool can be a solution to the problem, namely the need to display data on the vibration of the shooting hand to help the shooting training process at the Air Force Academy (AAU)